Effect of Blended Problem-Based Learning, Educator’s Blog and Student’s Indepedence on Human Reproductive System Learning Outcomes - Yusuf, Fauziah Wahyuni; Mustaji; Sitompul, Nurmida Catherine (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This research problem focuses on the low learning outcomes of students in the Human Reproductive System material, which the lack of variation in learning strategies and low student independence in learning can cause. This study aims to explore the effect of Blended Problem-Based Learning (PBL) assisted by educator blogs on biology learning outcomes on the topic of the Human Reproductive System and student learning independence. With a 2x2 quasi-experimental research design involving 144 grade XI students, the method of determining the control and experimental classes is by randomly drawing 2 classes by taking a roll of the control and experimental classes. The first is the control class, namely learning with the Expository Method, and the second is the experimental class, namely learning with Blended Problem-based learning Assisted by Educator Blogs. The determination of the sample in this study was carried out using a non-probability sampling technique. The technique used in this sample is saturated sampling. Data were collected through pre-and post-tests and analyzed using Two-Way ANOVA in SPSS 27. The results showed that Blended PBL significantly improved biology learning outcomes, especially in students with high learning independence. This study introduces a practical digital approach combining PBL with educators' online resources, providing insights into technology-based learning strategies that can improve students' academic outcomes according to their level of independence.